Curating dramaturgies
1 online resource
Keywords: "Curating Dramaturgies investigates the transformation of art and performance and its impact on dramaturgy and curatorship. Addressing contexts and processes of the performing arts as interconnecting with visual arts, the volume features interviews with leading curators, dramaturgs and programmers who are at the forefront of working in, with, and negotiating the daily practice of interdisciplinary live arts. The book offers a view of praxis that combines perspectives on theory and practice and looks at the way that various arts institutions, practitioners and cultural agents have been working to change the way that art and performance have developed, are displayed, and experienced by spectators and audiences in the last decade. Curating Dramaturgies argues that cultural producers and scholars are becoming more cognizant of this overlapping and transforming field. An essay by the editors explores the rise of interdisciplinary live arts and its ramifications in cultural and political terms. This is further elaborated in the interviews with 15 diversely placed arts professionals who are at the forefront of rethinking and consolidating a new field of the visual arts and performance"--